Growth pattern for body weight, hip height and body length of Brakmas cattle - A. W., Mohd Hafiz; Idris, Ismail; Yaakub, Halimatun (Asian Network for Scientific Information, 2014)
The objective of this study was to determine the growth pattern for body weight, hip height and body length using non-linear model and the correlation between the parameters in Brakmas cows. Cross-sectional data of body weight, hip height and body length of 363 heads of Brakmas cows were collected to determine the growth pattern using Brody and Gompertz growth model. The results showed that Gompertz growth function had the best goodness of fit to describe the growth of Brakmas cattle for body weight, hip height and body length as shown by its high coefficient of determination (0.96, 0.99 and 0.99, respectively). Brody model estimated higher mature sizes compared to Gompertz model as the rate of maturing derived by Brody model are lower for the parameters as shown by negative correlation between mature size and maturing. Body length-body weight has the highest correlation coefficient (0.95) and hip height-body weight showed the lowest relationship (0.92).